Crowdfunding and the Dynamics of Social Capital : A Systematic Literature Review - Singh, Dharmendra; Bansal, Rohit; Al-Dmour, Ahmed; Jha, Aruna; Malik, Garima (Indian Journal of Finance, 2025)
Purpose : The goal of the article was to synthesize the diverse literature on the dynamics of social capital in crowdfunding campaigns. Crowdfunding significantly benefits entrepreneurs as it democratizes funding avenues, empowering creators and entrepreneurs regardless of traditional financial constraints. Social capital in crowdfunding builds trust and extends campaign reach, turning backers into dedicated advocates—an element crucial for success. Methodology : This research conducted a hybrid systematic review of the existing literature by combining bibliometric and thematic analysis to synthesize crowdfunding and social capital research. This review presented a comprehensive analysis of 85 papers retrieved from the Scopus database to ascertain the prevailing research trends from 2014 to 2023. Network theory, signaling theory, and social identity theory served as the cornerstones of the present literature, and the authors built their conceptual research framework around them. Innovation attracted cash through crowdfunding, and the keyword analysis advocated that publicizing the business’s innovative qualities becomes easy with strong social capital and networks. Findings : With the help of bibliographic coupling, the study revealed four clusters within crowdfunding and social capital: Crowdfunding dynamics ; crowdfunding performance ; equity crowdfunding signals and social factors ; and SMEs, startups, and crowdfunding. The study also highlighted publication trends, prominent authors, journals, and articles in the given literature, which are highly useful for young researchers in this field. Practical Implications : This study offered valuable insights for entrepreneurs and crowdfunding campaign managers by emphasizing the strategic role of social capital in enhancing campaign visibility and backer trust. Originality : The originality of this research lay in its hybrid systematic review approach, which combined bibliometric and thematic analysis to comprehensively map the intersection of social capital and crowdfunding. By integrating network theory, signaling theory, and social identity theory, the study proposed a novel conceptual framework and identified emerging research clusters, filling a gap in synthesizing fragmented literature from 2014 to 2023.